Rethinking the Double Slit Experiment (Global Journal of Science Frontier Research, 2014)
The wave-particle duality relate to the space-time property of matter by Planck constant. The fine structure constant is linked to the double-slit and the uncertainty principle in Quantum Mechanics. Compton scattering and interference of doubleslit is established by the cross-linked angle T1 = Tc cos( θ2), and vice versa. The single-slit diffraction is described by Sincfunction which could combine the classical diffraction and quantum interference effect in the same experiment. This space-time model explain the experimental mystery of the double-slit.